Critical Evaluation of the Independent Teaching Platform in Improving Education Quality Considering Ivan Illich's 'Deschooling Society' Principles - Marianus Tapung (Jurnal Pendidikan Indonesia, 2024)
The integration of the Merdeka Mengajar Platform (PMM) in the Merdeka Belajar Curriculum aims to enhance the quality of education and self-development of teachers in Indonesia through an efficient online learning model. However, its utilization requires critical evaluation considering the challenges and negative impacts observed in practice. This study critically examines the use of PMM through the lens of Ivan Illich's "De-schooling Society" principles. Illich's critique emphasizes the risks of technological dependence, commodification of education, and the potential erosion of human relationships in learning environments. The research employs a literature review method, drawing on scientific journals, articles, books, and policy regulations. Findings highlight the relevance of Illich's concerns to the current use of PMM, including the potential for increased technological dependence, inequitable access, and diminished human interaction. Despite PMM's benefits in fostering professional development and collaborative practices, its uncritical application risks undermining social solidarity and perpetuating educational inequalities. The study concludes with recommendations for stakeholders to balance technological integration with human-centred educational practices. Emphasizing the need for inclusive access, careful monitoring, and alignment with the principles of independent, character-building education, the paper suggests ways to mitigate the adverse effects identified. Reflecting on Illich's vision, it calls for a cautious approach to ensure PMM contributes positively to educational goals.